Analysis of eating habits among women from rural and urban areas after becoming pregnant - Wójtowicz-Chomicz, Katarzyna; Majewska, Anna; Borzęcki, Andrzej (Polish Journal of Public Health, 2013)
Introduction. Improper eating habits among pregnant women may have a negative impact on fetal development and pregnancy. Balanced diet during pregnancy period should provide women with the right amount of energy as well as contain essential nutrients in the correct quantities and ratios. Aim. Evaluation of nutritional habits among pregnant women. Material and methods. The study was conducted among 100 pregnant women aged 21-38 years from urban and rural areas from different neighborhoods of Świdnik. Information on diet was obtained based on questionnaire survey. Results. Inadequate intake of fish and high intake of sweets was reported. Fruit and vegetables intake was found to be at satisfactory level. Habit of eating fast food products among expectant mothers remains as worrying issue. Conclusions. Among examined group of expectant mothers, incorrect eating habits such as getting on food between meals and insufficient consumption of fish was reported. It is important to carry out activities in the field of health education in perinatal care that promotes healthy eating.